Micro-Enterprise Development as a Coping Strategy for Food Insecurity in Humla District - Bhusal, M.; Regmi, P. P.; Dutta, J. P.; Thapa, R. B. (Economic Journal of Nepal, 2015)
In Nepal most of the micro-enterprises established so far are agro-based, forest-based and livestock-based. The practice of such enterprises has successful entrepreneurship. The major objective of this study was to access the micro-enterprise to cope with food insecurity in Humla district of Nepal. Food insecurity was major problem of Humla. Food sufficiency from own production in the district ranged from 3-9 months. This study helps to point out the relationship between food insecurity condition and role of the microenterprise. Forty households from each Village Development Committee (VDC), Khagalgaun and Simikot were interviewed. This study concluded that loan borrowed for micro-enterprise, food sufficiency of households, experience year in enterprise, female members in family and cropping area of household are considered the significant factors for income generation from micro-enterprise. Best possible micro-enterprise in the study area was non timber forest products related enterprise followed by fruits/vegetable/honey and handicrafts. The major problems of micro-enterprise were technological and marketing. To cope with food insecurity people of Humla were engaged in honey production followed by Non-timber Forest Products (NTFPs) production and collection, dropping children from school and some were engaged in fruits and vegetable production and few migrated from their settlements. Most products were sold in local market at low price demanding commercialization and diversification of products.The Economic Journal of NepalVol. 35, No. 4, October-December 2012 (Issue N0. 140)Page: 252-261